(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Igor V. Nefedov (Southern Federal University. Rostov-on-Don, Russian Federation) National radio, like television, is called upon to bring to the masses not only relevant information, but also a high culture of language. There were always serious demands to oral public speech from the point of view of the correctness and uniformity of the pronunciation. However, today the analysis of the language practice of broadcasting often indicates a discrepancy between the use of linguistic resources in existing literary norms. The author of the article from the end of December 2016 to early April 2017 listened and analyzed from the point of view of language correctness the majority of programs on the radio Komsomolskaya Pravda (KP). In general, recognizing the good speech qualification of the workers of this radio, as well as their «guests» (political scientists, lawyers, historians, etc.), one can not but note the presence of a significant number of errors in their speech. The material presented in the article allows us to conclude that at present, broadcasting is losing its position in the field of speech culture. Neglect of the rules of the Russian language on the radio «Komsomolskaya Pravda» negatively affects the image of the Russian language, which is formed in the minds of listeners. The language of radio should strive to become a standard of cleanliness and high culture for the population, since it has the enormous power of mass impact and supports the unity of the cultural and linguistic space. Key words: accentological, orthoepic, lexico-grammatical errors, broadcasting, language of radio. DOI 10.23683/1995-0640-2017-2-118-126